Land use and flood management one day conference : delegate literature pack : Thursday 30 January 2003 (Thomas Telford, 2003)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 30 January 2003.
Keywords: Flood control -- Congresses.; Land use -- Congresses.; Watershed management -- Congresses.; elektronické knihy; electronic books